Computer-mediated communication as an autonomy-enhancement tool for advanced learners of English - Wach, Aleksandra (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2012)
This article examines the relevance of modern technology for the development of learner autonomy in the process of learning English as a foreign language. Computer- assisted language learning and computer-mediated communication (CMC) appear to be particularly conducive to fostering autonomous learning, as they naturally incorporate many elements of autonomy that give learners control over and responsibility for their own learning, such as choosing the materials used, managing their contact with various genres and types of interaction, often in authentic contexts, and evaluating their own progress, measured through their success in understanding and conveying meanings. However, providing access to language resources does not automatically lead to the development of autonomy, as much depends on other factors, such as the learners’ level or previous experience in learner training. The present study investigated whether advanced learners of English made use of out-of-class CMC engagement for the purpose of learning English autonomously. The results indicate that most of the participants were eager to use CMC opportunities to deliberately practice their English, although, quite naturally, leisure and social reasons for using CMC predominated. The expressed willingness to deliberately focus on practicing English during beyond-theclassroom meaning-oriented online interactions confirms the great potential of CMC as an autonomy-enhancement tool.
Keywords: Computer-mediated communication (CMC); computer-assisted language learning (CALL); learner autonomy; learning beyond the classroom